POTENSI PENGGUNAAN BLOCKCHAIN DALAM MANAJEMEN HAK KEKAYAAN INTELEKTUAL DI INDONESIA: PELUANG DAN HAMBATAN - Girindra, Ida Ayu Vipra (Esensi Hukum, 2023)
The advancement of information technology has driven rapid progress in the field of Intellectual Property Rights (IPR) globally. However, this development has also given rise to new challenges in the realm of IPR. Presently, several countries have started leveraging blockchain technology in specific sectors. Blockchain is hailed for its accountability, security, transparency, and permanence. Its sophistication is seen to hold potential in various sectors, including IPR. This research aims to explore the opportunities and barriers of implementing Blockchain technology in IPR management in Indonesia. The study adopts a normative legal research approach, focusing on legislation and regulations. The findings indicate that Indonesia's current IPR management still has shortcomings that can be addressed through the capabilities offered by Blockchain technology. Nevertheless, there are several obstacles that must be overcome to ensure the responsible and secure development and implementation of this technology.